2001
DOI: 10.1055/s-2001-15451
|View full text |Cite
|
Sign up to set email alerts
|

Hypericum Extract and Hyperforin: Memory-Enhancing Properties in Rodents

Abstract: Effects of a Hypericum extract in therapeutic use and hyperforin sodium salt were evaluated in rat and mouse avoidance tests. In a conditioned avoidance response (CAR) test on the rat, oral daily administration of hyperforin (1.25 mg/kg/day) or of the extract (50 mg/kg/day) before the training sessions considerably improved learning ability from the second day onwards until the day 7. In addition, the memory of the learned responses acquired during 7 consecutive days of administration and training was largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 24 publications
4
46
0
Order By: Relevance
“…29 Avoidance tests suggest that Hypericum extract exhibits memory-enhancing properties, indicating that HF is involved in its cognitive effects, acting more as an antidementia agent than an antidepressant. 30 HF also increases the release of acetylcholine from rat hippocampus in vivo in a calciumdependent way, suggesting its potential therapeutic efficacy in central cholinergic dysfunction. 31 HF stimulates the processing of the amyloid precursor protein (APP) in rat pheochromocytoma PC12 cells transfected with human wild-type APP, with a transiently increased release of secretory APP fragments and a strong reduction of intracellular APP.…”
Section: Additional Neurological Effectsmentioning
confidence: 99%
“…29 Avoidance tests suggest that Hypericum extract exhibits memory-enhancing properties, indicating that HF is involved in its cognitive effects, acting more as an antidementia agent than an antidepressant. 30 HF also increases the release of acetylcholine from rat hippocampus in vivo in a calciumdependent way, suggesting its potential therapeutic efficacy in central cholinergic dysfunction. 31 HF stimulates the processing of the amyloid precursor protein (APP) in rat pheochromocytoma PC12 cells transfected with human wild-type APP, with a transiently increased release of secretory APP fragments and a strong reduction of intracellular APP.…”
Section: Additional Neurological Effectsmentioning
confidence: 99%
“…17 Besides its antidepressive activity, it has been suggested that HYP possesses memory-enhancing properties in rodents. 18 These antecedents drove us to investigate whether hyperforin derivatives would be able to reduce both the b-amyloid deposition and improve spatial learning acquisition. We used a rat model consisting of an intrahippocampal stereotaxic bilateral injection of preformed Ab fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a severe overdosage of St. John's wort extracts may have effects on motility and should be avoided, particularly in patients with disorders of the motor systems (e.g., Parkinson's disease). On the other hand, if the facilitatory action of hyperforin on ACh release is also present in other brain areas such as hippocampus or cortex, it may explain beneficial effects of hyperforin in learning and memory tests (e.g., scopolamine-induced amnesia; Klusa et al, 2001) and may form a basis for the use of hyperforin (and St. John's wort) in cognitive disorders . This possibility is currently under investigation in our laboratory.…”
Section: Inhibitory Effects Of Hyperforin On the Cholinergicmentioning
confidence: 99%